If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(p + 8) + 4p = 4 Reorder the terms: 4(8 + p) + 4p = 4 (8 * 4 + p * 4) + 4p = 4 (32 + 4p) + 4p = 4 Combine like terms: 4p + 4p = 8p 32 + 8p = 4 Solving 32 + 8p = 4 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-32' to each side of the equation. 32 + -32 + 8p = 4 + -32 Combine like terms: 32 + -32 = 0 0 + 8p = 4 + -32 8p = 4 + -32 Combine like terms: 4 + -32 = -28 8p = -28 Divide each side by '8'. p = -3.5 Simplifying p = -3.5
| 8-4xb=2xb | | 13=2x-5y | | 3y^2-5y+12=0 | | 5p+6=4p+8 | | -4-2x-6=-8 | | 1.4f+1.1=8 | | 5x-0.06=6x | | xy+3=w+15z | | 3+a=4a | | 6y+7+3y=3(3y-2)+13 | | 7x+7=4x-20 | | (8x-8)2-25=0 | | 6y+7+3y=3 | | x-5+x+.75x+.25x+3=360 | | 3t+7=-2t+27 | | y=-.5(4)-3 | | 6+-5x=-30 | | 16x+7=15+15x | | x-5+x+.75x+.25x+3=180 | | 7-4x-4(x-2)=-1 | | 9-2(x+3)=3 | | (98)x=6272 | | 2x-27=-15 | | 1.75c=7.5 | | 13y+19=6(9+1y)+18 | | y=-.5(2)-3 | | x^2-28x=-49 | | x+102=4*x | | 4-2(5-2x)=9-6x | | m^3-4m^2+5m-1=0 | | y=-.5(-2)-3 | | 3n/5=-20 |